Polybenzoxazine/Polyhedral Oligomeric Silsesquioxane (POSS) Nanocomposites - Mohamed, Mohamed Gamal (Polymers (Basel), 2016)
The organic/inorganic hybrid materials from polyhedral oligomeric silsesquioxane (POSS, inorganic nanoparticles) and polybenzoxazine (PBZ) have received much interesting recently due to their excellent thermal and mechanical properties, flame retardance, low dielectric constant, well-defined inorganic framework at nanosized scale level, and higher performance relative to those of non-hybrid PBZs. This review describes the synthesis, dielectric constants, and thermal, rheological, and mechanical properties of covalently bonded mono- and multifunctionalized benzoxazine POSS hybrids, other functionalized benzoxazine POSS derivatives, and non-covalently (hydrogen) bonded benzoxazine POSS composites.